TINJAUAN YURIDIS TINDAK PIDANA KEKERASAN TERHADAP ANAK DARI PERSPEKTIF HUKUM PIDANA NASIONAL DAN HUKUM PIDANA ISLAM - Rhizkita Ramadhana; Erdianto Effendi; Adi Tiara Putri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Violence against children in Indonesian national law is a crime. Violence against children is often identified with invisible violence, such as physical and sexual violence. In fact, psychological and social (structural) violence also has a negative and permanent impact on children. In Islamic Law, physical violence against children includes the act of Jarimah (Arabic), which is an unlawful act in which the offender receives a sanction or punishment . Besides that basically all religions reject violence as a principle in carrying out an act of immoral nature that requires coercion of other parties which means violation of the principle of freedom of social interaction.This type of research can be classified into normative juridical type of research, namely research conducted by examining literature discussion with secondary data sources consisting of primary legal material in the form of legislation, secondary legal materials, legal books, and tertiary legal materials in the form of dictionaries. Then the data were analyzed qualitatively, namely analyzing descriptive data obtained from secondary data.From the results of the study it can be concluded that, first, if in national law the types or forms of violence are categorized into two, namely severe maltreatment and minor maltreatment. Whereas in Islamic criminal law, violence is categorized into three, namely deliberate maltreatment, semi-deliberate maltreatment, and inadvertent maltreatment. The form of sanctions that are applied in national law for acts of violence against children is regulated in Article 80-82 of Law Number 35 Year 2014 concerning Child Protection, and in Islamic criminal law sanctions are given according to the category of violence, which can be in the form of qishas, diyat punishment, or ta'zir punishment. Second, the value of regulating children in the Islamic criminal law system when compared with positive law both have many significant differences. Values that can be adopted into national law, one of which is the application of penalties / sanctions to perpetrators by applying the qishas penalty, diyat punishment, or ta'zir punishment, legal protection for victims of crime as part of protection to the public, can be realized in the form of providing compensation directly to child victims not to the State.Keywords: Criminal Acts - Violence in Children - National Law - Islamic Criminal Law